2020
DOI: 10.32615/ps.2019.181
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Can we predict winter survival in plants using chlorophyll a fluorescence?

Abstract: In the last years, JIP-test became to be a tool widely applied to assess the performance of photosynthetic apparatus of plants growing under environmental stresses. The objective of our work was to check whether JIP-test can help to predict winter survival in plants. An experiment with outdoor vertical garden was conducted in June 2015 on a south-oriented wall in Lublin city, Poland. Plants were cultivated in pockets made of polyester felt and irrigated by automatic controlled system. After winter period (2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Evergreen Mediterranean plants exposed to winter stress often show reduced maximum quantum efficiency and quantum yield of PSII electron transport (Φ PSII ) ( Vitale et al., 2012 ). In contrast, Swoczyna et al. (2020) found that neither F V /F M nor PI ABS , but parameters related to PSII reaction centres, showed significant correlations with winter survival of woody plants and perennials cultivated in a vertical garden on the wall of an urban building.…”
Section: Chlorophyll a Fluorescence Measurements I...mentioning
confidence: 65%
See 1 more Smart Citation
“…Evergreen Mediterranean plants exposed to winter stress often show reduced maximum quantum efficiency and quantum yield of PSII electron transport (Φ PSII ) ( Vitale et al., 2012 ). In contrast, Swoczyna et al. (2020) found that neither F V /F M nor PI ABS , but parameters related to PSII reaction centres, showed significant correlations with winter survival of woody plants and perennials cultivated in a vertical garden on the wall of an urban building.…”
Section: Chlorophyll a Fluorescence Measurements I...mentioning
confidence: 65%
“…(2014) found that the appearance of the K-band indicated disturbances in the oxygen-evolving complex but at the later stage of ageing. It has also been noted that during the growing season, the strength of the ChF signal may decrease ( Swoczyna et al., 2020 ; Suchocka et al., 2021 ), reflected in decreased F 0 and F M in the late season, and is not caused by leaf physiology, but rather by morphological changes, i.e., thickening of the cuticle, etc. In evergreen conifers and deciduous trees, differences between the different age classes are to be expected.…”
Section: Chlorophyll a Fluorescence Measurements I...mentioning
confidence: 99%